ASSESSMENT AND MANAGEMENT OF SEVERE GASTROINTESTINAL SYMPTOMS IN THE ADULT PATIENTS WHEN PROVIDING PALLIATIVE CARE - A. V. Beloborodova; D. V. Nevzorova; Zh. M. Sizova; E. A. Bakunina (Вестник анестезиологии и реаниматологии, 2018)
According to calculation methods recommended by World Health Organisation, in Russia, approximately 600,000 people (from 378,46 to 561,52 per 100,000 population) are need of palliative care. Palliative care includes various medical interventions aimed at pain relief and management of other severe manifestations of the disease, life quality improvement of incurably ill citizens and this care can be provided on the out-patient and in-patient basis by medical workers who had training in the provision of such care (pp. 36 of FZ-323). Due to the above, it is necessary to work out standard approaches to assessment and management of main severe symptoms in the patients in need of palliative care. The article discusses the opportunities for management of severe gastrointestinal symptoms in the adults patients in need of palliative care with life expectancy from several weeks to several years. Pharmacological and non-pharmacological methods, individual approach attentive to details are to be combined for the effective management of severe events.